A network meta-analysis of efficacy and safety of adjuvant targeted therapy or immunotherapy in non-small cell lung cancer - Sunatee Sa-nguansai; Sasivimol Rattanasiri; Prapaporn Pornsuriyasak; Pawin Numthavaj; Gareth J. McKay; John Attia; Ammarin Thakkinstian (Scientific Reports)
Abstract The integration of targeted therapy and immunotherapy into adjuvant treatments for early-stage non-small cell lung cancer (NSCLC) remains challenging. This study aimed to compare the efficacy and safety of all available adjuvant treatment options. Randomized controlled trials (RCTs) published up to August 15, 2023, were identified from MEDLINE, Scopus, and Cochrane CENTRAL. RCTs were included if they studied early-stage NSCLC and compared any adjuvant systemic targeted therapy or immunotherapy with adjuvant chemotherapy/placebo. This study was registered with PROSPERO, CRD42022351290. Individual patient data were generated based on data extracted from Kaplan–Meier curves. A parametric survival model was used to estimate the median time for disease-free survival (DFS) and overall survival (OS). A two-stage network meta-analysis (NMA) was applied to estimate the hazard ratio (HR) for DFS and OS, in addition to the risk ratio (RR) of severe adverse events (SAE). Nineteen RCTs (n = 9,438) were included for assessing the effects of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), vascular endothelial growth factor (VEGF) inhibitors, immune checkpoint inhibitor (ICI) immunotherapy, and non-ICI immunotherapy. DFS in EGFR-TKIs and ICI immunotherapy was longer than chemotherapy/placebo, with a median time of 69.24, 53.47, and 39.49 months, respectively. EGFR-TKIs had a 46% significantly lower risk of recurrence [HR = 0.54 (95% CI: 0.38, 0.77)] than chemotherapy/placebo. Both EGFR-TKIs and ICI immunotherapy appeared to improve OS compared to chemotherapy or placebo, but both treatments also had an increased risk of SAE; however, neither result was statistically significant. This study indicates that EGFR-TKIs might be the best treatment regimen for reducing recurrence with an intermediate risk of SAE.